Improving Sepsis Compliance With Human Factors Interventions in a Community Hospital Emergency Room. - Kiser, Megan (Patient Safety (2689-0143), 2023)
Background: Adherence to best practices for sepsis management at a small community hospital was below system, state, and national benchmarks and affected vital indicators, including mortality. This study aimed to improve sepsis best practice compliance by implementing human factors-influenced interventions. Methods: The Plan-Do-Study-Act quality improvement methodology was used for this project. Baseline metrics included sepsis bundle compliance following CMS (Centers for Medicare & Medicaid Services) core measure standards, hospital mortality, sepsis triage screening, and physician order set use. Interventions: Several human factors workflows and tools were used to boost early identification with screening opportunities and enhance staff awareness of sepsis indicators. Results: With the interventions, the hospital's compliance with sepsis best practice treatment improved by a 23 percentage-point increase from baseline. Sepsis triage screening also increased and remained consistent after project interventions. Conclusions: With the project, using human factors tools enhanced staff engagement and increased sepsis awareness. Engagement increased sepsis identification and screening in a small community hospital setting.